A conversion-type electrochemical artificial synapse for plasticity modulation and dendritic application. (20th October 2020) - Wei, Huanhuan; Yu, Haiyang; Gong, Jiangdong; Li, Renjie; Han, Hong; Ma, Mingxue; Guo, Kexin; Xu, Wentao
Abstract : A conversion-type electrochemical artificial synapse exhibits potential applications for memory enhancement and dendritic integration; ultra-high sensitivity (3 mV) and extremely low-power consumption (32 fW) could be achieved. Abstract : Herein, a conversion-type electrochemical artificial synapse (ECAS) that integrates a solid-state polymer electrolyte with a nanostructured particle film is first designed and fabricated. The device emulates important synaptic functions, which can be adjusted by changing the amplitude, frequency, duration, and number of presynaptic spikes. The ECAS exhibits a dendritic integration that can be used to emulate biological networks. Moreover, the device exhibits the most sensitive impulse response (3 mV) and a competitive power consumption (32 fW), which are magnitudes lower than those of a biological synapse. This new ECAS design strategy and high-performance device pave the way for future low-power and ultrasensitive brain-inspired electronics.